Coexistence of Histologically Confirmed Hashimoto's Thyroiditis with Different Stages of Papillary Thyroid Carcinoma in a Consecutive Chinese Cohort. (18th November 2014) - Liu, Xiaoyun; Zhu, Lijun; Cui, Dai; Wang, Zhixiao; Chen, Huanhuan; Duan, Yu; Shen, Meiping; Wu, Yunsong; Rong, Rong; Zhang, Zhihong; Wang, Xiaodong; Chen, Jiawei; et al.
Abstract : Purpose . To determine the relationship between Hashimoto's thyroiditis (HT) and all stages of papillary thyroid carcinoma (PTC) with or without local lymph node metastasis (LNM). Methods . We conducted a retrospective study of thyroidectomies from 2008–2013 in First Affiliated Hospital of Nanjing Medical University. We categorized patients according to the presence of histopathologically proven HT. The prevalence of mPTC (maximum diameter ≤ 10 mm) and crPTC (clinical relevant PTC) and local LNM rates were compared. Results . We evaluated 6, 432 consecutive thyroidectomies. In total, 1, 328 specimens were confirmed as HT. The prevalence of PTC in this HT cohort was 43.8%, significantly higher than non-HT group. After adjustment of gender and age, the prevalence of PTC was still higher in HT group. HT was a risk factor for PTC in multivariate analysis with odds ratio 2.725 (95% CI, 2.390–3.109) (P < 0.001 ). However, no correlation was found between HT and LNM of PTC. Conclusion . HT was associated with an increased prevalence of all stages of PTC, independent of tumor size, gender, and age. In contrast, locally advanced disease defined by LNM was unrelated to HT. These data suggest an association of HT with low risk PTC and a potential protective immunologic effect from further disease progression.